PENGEMBANGAN POTENSI LOKAL PERTANIAN UNTUK PENINGKATAN EKONOMI MASYARAKAT: STUDI PADA HOME INDUSTRI JAPRI DI PEKON PRINGSEWU, LAMPUNG - Lia Widya Listiawati (Journal Tafkirul Iqtishodiyyah, 2025)
This study aims to analyze the development of a home industry based on local agricultural potential under the Japri brand and its impact on improving the economic conditions of the community in Pekon Pringsewu. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation involving the management and members of the home industry. The findings indicate that the development process includes socialization, mapping and introducing local potential such as bananas, cassava, and sweet potatoes, providing production skill training, and establishing small business groups as collaborative working units. The results further reveal that the participation of community members particularly housewives in Japri’s production activities has significantly increased their daily income, which was previously unstable and dependent solely on their husbands’ earnings or seasonal harvests. Additionally, the home industry has fostered economic independence, women’s empowerment, and the optimal utilization of local resources. The study also shows that Japri’s progress is supported by the availability of abundant local raw materials and development strategies based on hands-on training and intensive mentoring. Thus, it can be concluded that the development of a home industry based on local potential plays a crucial role in enhancing community welfare, although this study is limited by its narrow geographical focus and reliance on qualitative data. Future research is recommended to adopt a mixed-method approach and expand the analysis to include marketing aspects, policy implications, and business sustainability.